2013
DOI: 10.1007/s00192-013-2242-4
|View full text |Cite
|
Sign up to set email alerts
|

What is the best indication for single-incision Ophira Mini Sling? Insights from a 2-year follow-up international multicentric study

Abstract: Introduction and hypothesisThe Ophira Mini Sling System involves anchoring a midurethral, low-tension tape to the obturator internus muscles bilaterally at the level of the tendinous arc. Success rates in different subsets of patients are still to be defined. This work aims to identify which factors influence the 2-year outcomes of this treatment.MethodsAnalysis was based on data from a multicenter study. Endpoints for analysis included objective measurements: 1-h pad-weight (PWT), and cough stress test (CST),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Ajust, a recently developed SIMS, has an added advantage that allows post-anchorage adjustment of the sling tension [14]. This polypropylene anchor design has been shown in independent animal studies assessing its immediate and delayed extraction forces to be associated with the strongest and most robust mechanism anchoring it to the obturator complex [14,20]. Our current study confirmed the security of the use of SIMS-Ajust in the management of female SUI, compared with conventional standard transobturator midurethral slings (SMUSAlign), suggesting that SIMS-Ajust is one of the best choices in the management of female SUI during at least the 1-year follow-up period.…”
Section: Discussionmentioning
confidence: 98%
“…Ajust, a recently developed SIMS, has an added advantage that allows post-anchorage adjustment of the sling tension [14]. This polypropylene anchor design has been shown in independent animal studies assessing its immediate and delayed extraction forces to be associated with the strongest and most robust mechanism anchoring it to the obturator complex [14,20]. Our current study confirmed the security of the use of SIMS-Ajust in the management of female SUI, compared with conventional standard transobturator midurethral slings (SMUSAlign), suggesting that SIMS-Ajust is one of the best choices in the management of female SUI during at least the 1-year follow-up period.…”
Section: Discussionmentioning
confidence: 98%
“…The Ophira (Promedon) and MiniArc ® (Astora) trials reported 86.3% and 84.5% negative CST results, respectively, at 2‐years. One‐hour pad weight testing was used in both the Ophira and MiniArc trials to evaluate objective effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 94 of the 113 (83.2%) enrolled subjects were available for their 24‐month follow‐up. In comparison to the single incision sling studies referenced above, the Ajust trial had 92/95 (96.8%) subjects available at 24‐months, the Ophira study had 95/124 (76.6%), and the Miniarc trial had 134/188 (71.3%) and carried forward an additional eight known failures. It is well known that completer analyses may provide optimistic estimates of treatment effects.…”
Section: Discussionmentioning
confidence: 99%
“…This prospective, single-arm, open-label study was conducted to access clinical outcomes of Ophira Mini-sling System either in inpatient or outpatient basis for the treatment of female SUI in a single center, performed as described before [8]. The institutional board approved the study and all patients signed informed consent.…”
Section: Methodsmentioning
confidence: 99%